Teaching Styles, Learning Styles, and Reading Comprehension Levels: Bases for a Reading Awareness Guide - Casas, Rhea Belle (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship among teaching styles, learning styles, and reading comprehension levels of Grade 7 learners in selected schools in Carmen and Sogod, Cebu, as bases for developing a Reading Awareness Guide. Anchored on Sociocultural Theory, the VARK Learning Style Model, and the Every Child a Reader Program, the study employed a mixed-methods design involving 175 respondents composed of Grade 7 learners and English teachers. Data were gathered using demographic questionnaires, the VARK Learning Styles Questionnaire, the VARK Teaching Styles Questionnaire, the Philippine Informal Reading Inventory, and semi-structured learner interviews. Findings revealed that auditory learning was the most dominant learning style among learners, and most learners were unimodal. Teachers demonstrated varied VARK-based teaching styles, with three teachers’ styles aligned with most learners’ preferences and one showing misalignment. Despite this partial alignment, learners generally showed low to moderate reading comprehension, with critical comprehension identified as the weakest area. The study also found that vocabulary difficulty, text complexity, smartphone distractions, family support, reading environment, and learner interest affected reading comprehension. The study concludes that teaching-learning style alignment may support engagement but is not sufficient alone to improve comprehension. It recommends differentiated instruction, vocabulary support, critical reading activities, learner self-awareness, family involvement, and school-based reading awareness initiatives. The study supports SDG 4 – Quality Education by promoting literacy development, inclusive instruction, and learner-centered reading support. Its sustainability impact lies in strengthening educational and institutional practices through evidence-based reading interventions and adaptive teaching strategies.